2005
DOI: 10.1111/j.1475-4983.2005.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of Hyolithids and Its Functional Implications

Abstract: The exceptionally preserved hyolithids Gompholites striatulus, Maxilites robustus, Maxilites snajdri and Maxilites sp. are described with particular emphasis on helen and muscle scar morphology. These two aspects of hyolithid morphology have remained controversial. In life position, each helen curved ventrally. When the operculum closed the aperture of the conch, each helen was locked at the commissure slit with its dorsal edge tilted forward. Inside the conch, it was held in the dorsal apertural plane and cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 10 publications
0
52
0
Order By: Relevance
“…Looking more widely, the paired muscle scars and shelly internal projections evident in Morph A valves of Oikozetetes 51,52 , some of the best documented halkieriid shells, have possible parallels in the equivalent paired muscle scars and internal processes present in the mitral sclerite of the tommotiids Micrina 44 and Dailyatia 35 and the operculum of hyolithids 53 (potential relatives of tommotiids 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Looking more widely, the paired muscle scars and shelly internal projections evident in Morph A valves of Oikozetetes 51,52 , some of the best documented halkieriid shells, have possible parallels in the equivalent paired muscle scars and internal processes present in the mitral sclerite of the tommotiids Micrina 44 and Dailyatia 35 and the operculum of hyolithids 53 (potential relatives of tommotiids 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…In its simplicity, the outer surface of this operculum is reminiscent of Maxillites Marek, from the middle Cambrian of the Czech Republic, but there is no indication of the complex structure of the inner surface described by Marek () and Martí Mus & Bergström (). Although flattened and broken, it is slightly wider than tall, with the widest point at just below mid‐height; the initial growth stage and summit is at just above two‐thirds height.…”
Section: Hyolithellus Sp
Figure T Y–aamentioning
confidence: 99%
“…In Maxillites from the Czech Republic, the summit is located lower on the shield with the cardinal surface up to half of the height (Marek ; Martí Mus & Bergström ). An operculum of Hyolithus oelandicus Holm, from the middle Cambrian of Borgholm, Sweden, referred to Maxillites by Marek (), was only tentatively placed within that genus by Malinky & Berg‐Madsen () on account of the lack of information concerning its interior surface.…”
Section: Hyolithellus Sp
Figure T Y–aamentioning
confidence: 99%
“…stationary at the aperture of the conch, only opening at the ventral margin (Marek 1967;Marti-Mus and Bergström 2001), the opercula of orthothecids were small enough to fit inside the conch and apparently were capable of vertical movement within it (Marek 1966;Marek and Yochelson 1976). While hyolithids apparently relied on muscles to move the operculum and conch in relation to each other (Marti-Mus and Bergström 2001), orthothecids may have relied on hydrostatic mechanisms to manipulate their skeletal parts.…”
Section: Hyolithida and Orthothecidamentioning
confidence: 97%
“…The opercula of hyolithids also have two sets of internal processes; a set of teeth-like structures (cardinal processes) situated close to the dorsal margin and a set of ridge-like structures (clavicles) running from the cardinal processes towards the ventral side. Diverse muscle scar patterns are present in certain hyolithid opercula, and Marek (1963Marek ( , 1967 and Marti-Mus and Bergström (2001) suggested that some at least (including scars associated with the cardinal processes) were involved in controlling the movement of the operculum with reference to the conch. Other scars were interpreted by Marti-Mus and Bergström (2001) as structures involved in controlling the position and movement of the helens.…”
Section: Hyolithida and Orthothecidamentioning
confidence: 97%